Management of hunting waste as control measure for tuberculosis in wild ungulates in south‐central Spain. Issue 5 (13th March 2018) - Cano‐Terriza, D.; Risalde, M. A.; Jiménez‐Ruiz, S.; Vicente, J.; Isla, J.; Paniagua, J.; Moreno, I.; Gortázar, C.; Infantes‐Lorenzo, J. A.; García‐Bocanegra, I.
Summary: In recent decades, habitat change and the intensive management of wild ungulates for hunting have led to an increase in their populations in south‐central Spain. This implies a higher generation of hunting waste, which can favour the transmission of infectious diseases, including tuberculosis (TB). The aim of this study was to assess the usefulness of the proper disposal of hunting waste as TB control measure in wild boar ( Sus scrofa ) and red deer ( Cervus elaphus ) during the 2008/2009 to 2016/2017 hunting seasons. Blood samples from 664 wild boar and 934 red deer were obtained in 14 game estates in two provinces in Andalusia (Area 1), where the disposal of hunting waste was implemented since the 2012/2013 hunting season. Besides, six game estates in the province of Ciudad Real, in Castilla‐La Mancha (Area 2), an adjacent region where this management measure was not implemented during the studied period, were used as controls, sampling 277 wild boar and 427 red deer sera. The Mycobacterium tuberculosis complex (MTC), seroprevalence detected in wild boar from Area 1, was significantly higher before the disposal of big game hunting by‐products (82.8%; 2008/2009–2012/2013) compared to the second period (61.8%; 2013/2014–2016/2017) ( p  <   .001), after this control measure became established. By contrast, no significant differences between periods were found in wild boar (41.3% versus 44.8%; p  =   .33) and red deer (14.9% versus 11.6%; p  =   .19) from Area 2 as well as in red deer (10.8% versus 10.5%; p  =   .48) from Area 1. The proper disposal of hunting waste contributed to achieve a 25% reduction in MTC seroprevalence in wild boar. These results are of particular relevance regarding wild boar in the current context of re‐emerging and emerging diseases such as TB and African Swine Fever in Europe. Further studies are needed to assess the effect of this measure on the health status of livestock and other wildlife species.